PENGARUH SUBSTITUSI DEDAK HALUS DENGAN TEPUNG KULIT BUAH KOPI DALAM RANSUM TERHADAP KECERNAAN ENERGI DAN PROTEIN PADA TERNAK BABI FASE GROWER - Kaligis, fransiska; Umboh, J. F.; Pontoh, Ch. J.; Rahasia, C. A. (Universitas Sam Ratulangi, 2017)
EFFECT OF SUBSTITUTION OF RICE BRAN WITH COFFEE HUSK MEAL IN THE DIETS ON ENERGY AND PROTEIN DIGESTIBILITY OF GROWING PIGS. A study was conducted todetermine the effects of substitution of rice bran with coffee husk meal in the diets on energy and protein digestibility of growing pigs. The present study was conducted for 60 days, using 20 castrated male Duroc X Spotted Poland China, aged 2.5–3.0 months with an averaged body weight of 30.1–40.0 kg. Treatment diets were formulated as follow: R0 = 25% rice bran + 0% coffee husk meal (without coffee husk meal); R1 = 18.75% rice bran + 6.25% coffee husk meal (substitution of 25%); R2 = 12.5% rice bran + 12.5% coffee husk meal (substitution of 50%); R3 = 6.25% rice bran + 18.75% coffee husk meal (substitution of 75%); and R4 = 0% rice bran + 100% coffee husk meal (substitution of 100%). Completely Randomized Block Design (CRBD) with 5 treatments and 4 replications (blocks) was used as a statistical analysis (Anova). An Orthogonal Contrast test was further employed to analyze treatment differences. Different between treatment (s) was declared at P < 0,05. Parameters measured were energy and protein digestibility. Research results showed that there was no significant differences (P > 0,05) were found among treatments on energy and protein digestibility. It can be concluded that coffee husk meal can be used up to 100% to replace rice bran or 25% in the diets of growing pigs.Key words: Pig, rice bran, coffe husk, energy, protein digestibility